TiGa–VN complexes in GaN: a new prospect of carrier mediated ferromagnetism. Issue 106 (19th October 2015) - Majid, Abdul; Javed, Mehreen; Rana, Usman Ali; Khan, Salah Ud-Din
Abstract : First principle investigations exploring the effects of nitrogen vacancies on ferromagnetism in Ti doped wurtzite GaN are reported. Abstract : First principle investigations exploring the effects of nitrogen vacancies on ferromagnetism in Ti doped wurtzite GaN are reported. The presence of nitrogen vacancies demonstrated no noticeable effect in the case of pure GaN but exhibited ferromagnetism in the case of Ti doped GaN. The magnetic moment however ceased upon doubling the concentration of dopant and vacancies in the host which points towards possible antiferromagnetic coupling. The conventional double exchange ordering observed in the case of the vacancy-added Ti:GaN switched to a carrier mediated exchange for the TiGa –VN complex in Ti:GaN. For Ti doped GaN, the energy difference calculated with and without N vacancies is found to be relatively smaller than that of other 3d transition metal (Cr, Mn, Fe, Co, Ni, Cu) doped GaN. The results calculated for different configurations to explore the effects of nitrogen vacancies on the electronic and magnetic properties of Ti:GaN are discussed in detail.